PENGARUH PERHATIAN ORANGTUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS IV SD NEGERI 097350 PARBUTARAN SIMALUNGUN - Saurma Sihombing; Regina Sipayung; Darinda Sofia Tanjung (Universitas Negeri Medan, 2020)
This study aims to determine the effect of parental attention on student learning outcomes in mathematics class IV at SD Negeri 097350 Parbutaran Simalungun in the learning year 2020/2021. In the research, researchers used quantitative methods. The population of this study were all fourth grade students of SD Negeri 097350 Parbutaran Simalungun, totaling 32 people. The research sample of 32 people was determined using the Non Probability Sampling technique, namely total sampling so that all members of the population as the research sample used the t-test on SPSS ver 22.0. The results of this study indicate that the results of correlation testing can be seen in the correlation coefficient value of 0.732 which means rcount (0.732) ≥ rtable (0.349), then Ha is accepted. So there is a strong influence between parental attention on student learning outcomes in grade IV SD Negeri 097350 Parbutaran Simalungun. It can also be seen from the results of the t-test hypothesis testing where tcount ≥ ttable, namely 5.891 ≥ 1.697, so it states that the hypothesis Ha is accepted. This shows the effect of parental attention on student learning outcomes in grade IV SD Negeri 097350 Parbutaran Simalungun for the 2020/2021 academic year.Keywords: Influence, Parental Attention, Learning Outcomes